(untitled) (Physical Culture and Sport: Scientific Perspective, 2025)
In the article, based on the study of scientific literature, an analysis of the works on the impact of physical exercises on the human body was carried out. It is noted that physical exercises have a huge educational value, contribute to strengthening discipline, increasing the sense of responsibility, and developing perseverance in achieving the set goal. In the study, motivation for physical exercises is defined as a need for various aspects of activity. Young people are quite interested in the aspect of aesthetics and beauty of the human body and the perfection of pyxis, which determines the personal perception of one’s personality through the physical state as a harmony of physical and spiritual development. It was found out that in order to attract the younger generation to physical exercises, it is necessary to apply certain measures that would increase the number of people willing to exercise. It is emphasized that in order to form a stable habit of physical exercises and types of motor activity, it is necessary to prove the expediency of physical exercises at leisure, to develop and maintain a constant interest in active activities, and to cultivate the habit of active recreation. Formation of motivation for active leisure among young people requires an understanding of the balance between internal and external incentives. In pedagogical concepts, priority should be given to internal motivation, which ensures stability and awareness in the choice of activities. External motivation, in turn, should be used as a tool for initial involvement of young people in useful activities. Thanks to this, it is possible to raise a generation that not only leads an active lifestyle, but also realizes its value and importance. After all, the motivation for physical exercises is not only about striving for an ideal shape, but also about taking care of yourself and your health. You should choose your favorite activity, maintain regularity and achieve your goal.